The effect of menopause on cardiovascular risk factors according to body mass index in middle-aged Korean women - Do Kyeong Song; Young Sun Hong; Yeon-Ah Sung; Hyejin Lee (PLoS ONE, 2023)
Background Menopausal status and obesity are associated with an increased risk for cardiovascular diseases. However, there are few studies on the effect of menopause on cardiovascular risk factors according to the degree of obesity during the menopausal transition. We aimed to evaluate the effect of menopause on cardiovascular risk factors according to body mass index (BMI) in middle-aged Korean women. Methods We analyzed 361 postmenopausal women and 758 premenopausal women (age: 45–55 years) without diabetes mellitus, hypertension, or dyslipidemia, using a cohort database released by the Korean National Health and Nutrition Examination Survey 2016–2018. Subjects were divided into two groups based on BMI. Women who underwent a hysterectomy or were pregnant were excluded from this study. Differences between groups adjusted for age and BMI were assessed. Results Postmenopausal women (52 ± 2 years) were older than premenopausal women (48 ± 2 years), and BMI did not differ between the two groups (22.8 ± 2.9 vs. 23.0 ± 3.1 kg/m2). After adjustment for age and BMI in total and non-obese subjects (not obese subjects), postmenopausal women exhibited higher hemoglobin A1c and total cholesterol levels than premenopausal women. Subgroup analysis for 138 postmenopausal and 138 age- and BMI-matched premenopausal women showed that postmenopausal women had higher total cholesterol levels than premenopausal women with marginal significance (201 ± 25 vs. 196 ± 27 mg/dL). Conclusion Menopausal status was associated with increased glucose and cholesterol levels independent of age and BMI in middle-aged Korean women. Menopausal status showed a significant relationship with increased total cholesterol levels even after adjusting for age and BMI in non-obese women but not obese women. Therefore, intensive monitoring and treating of lipid status is necessary to prevent cardiovascular events during the menopausal transition, especially in non-obese subjects.